O perfil dos trabalhadores das usinas do Madeira no estado de Rondônia entre os anos de 2009 e 2012 - Lima, Breno Azevedo (2015)
The objective of this thesis is to analyze the worker profile that came to Rondônia attracted by the hydropower plants of Rondônia between the years 2009 and 2012,, perpetrated by labor, beyond the social impact to the community. To understand this reality accessed poured the ontological standard and Marxian methodology, as theoretical framework. Focused categories were the arrival of the plants and its historical process of setting up and subsequent seduction and labor migration, the profile identified through the labor and the likely repercussions predictive. The methodological tool used to access the reality were focused labor demands and its wealth of data on worker qualification as a proponent , through qualitative analysis method, by analyzing the documents of the labor process.